Ботаника: пособие для учителей / П. А. Генкель, Л. В. Кудряшов - Генкель Павел Александрович (Просвещение, 1964)
Экземпляры: КХ (20150710) / Инвентарный номер: 373528 / Цена: 1.75 / Сис.шифр: 58 / Авт.знак: Г 34 / ГРНТИ: 34 / ББК: 28